August Kirschmann and the Material Culture of Colour in Toronto’s Early Psychological Laboratory - Weidenhammer, Erich (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2015)
Between 1893 and 1908, the German-born psychologist August Kirschmann (1860- 1932) led the University of Toronto’s newly founded psychological laboratory. Trained by the founder of experimental psychology, Wilhelm Wundt (1832-1920) Kirschmann was among an early generation of psychologists who helped to establish new laboratories across Europe and North America. Kirschmann’s main area of study was colour perception—a vital field during a period in which the technology of colour and illumination was advancing rapidly. This paper explores Kirschmann’s contribution through the material culture of his research in Toronto—especially instruments based on the technology of disc mixture. It discusses the exchange of experimental technology between Germany, where commercial manufacture of laboratory instruments was underway, and Toronto. It also explores Kirschmann’s technological contribution to his field. It cites, where possible, surviving objects and materials.